Trunk muscles co-activation patterns during exercises with oscillatory pole - Marques, Nise Ribeiro [UNESP] (2012)
This study aimed to compare trunk muscle co-activation pattern during exercises using an oscillatory pole. Twelve volunteers participated in this study, in which they performed three different exercises. EMG activity of internal oblique (IO), external oblique (EO), rectus abdominis (RA), multifidus (MU) and iliocostalis lumborum (IL) was collected. The EMG signals were analyzed in time domain (RMS) and muscles activation ratios were computed as follow: anterior-posterior (A/P=RA+EO+IO/MU+IL), MU/IL and OE/OI. The bilateral oscillation of the pole in frontal plane (exercise II) promoted a higher value of MU/IL ratio than unilateral oscillation of the pole in sagital plane (exercise III). Also, the bilateral oscillation of the pole in frontal plane (exercise II) and the unilateral oscillation of the pole in sagital plane (exercise III) caused higher values of the IO/EO than bilateral oscillation of the pole in transversal plane (exercise I). Thus, the exercises II and III required higher activation of trunk stabilizer muscles, being more indicate for training, which aims higher recruitment of these muscles in daily activities.